Competency Enhancement of Alumni Teaching Profession With Training in The Development of PBL and PJBL Learning Devices Based on Information and Communication Technology (ICT) - Sugiarto, Tatok; Arief Darmawan; Eko Hariyanto; Zihan Novita Sari; Ahadi Priyohutomo; Linggo Jiventino Yono Prayogo (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
Increasing competence is a necessity in the field of education, increasing competence possessed by a person will increase a certain amount of knowledge, therefore the importance of increasing competence for teachers is an effort to harmonize learning patterns and the education system as a whole. In the systematic planning of learning, the preparation of learning devices is an obligation that must be owned by a teacher before carrying out the process of teaching and learning activities, teachers who have good competence if they can make, develop, design and implement learning devices, therefore the preparation of learning devices should be adapted with the needs of students, PJBL and PBL. The methods in this service consist of the lecture method, mentoring, measurement of results. The results in this service are that the teacher has an understanding of the syntax of the learning model, and the differences in the PBL and PJBL work systems, broadens horizons in making teaching modules that suit student needs, can analyze and apply the PBL and PJBL methods in each learning activity, PJOK educators have better understanding of concepts, procedures, and evaluation in developing learning tools adapted to the implementation of the independent curriculum.